2006
DOI: 10.2527/2006.84132x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic relationships of farrowing and weaning survival to birth and placental weights in pigs1

Abstract: Data obtained during 4 generations of divergent selection for placental efficiency were used to determine factors influencing survival at farrowing and weaning in litters produced by first-parity females. Data were collected from 193 litters and included records on 2,053 individuals. Farrowing survival (FS) and weaning survival (WS) were considered traits of the piglet and were scored 1 if the individual was alive at a time point or 0 if dead. Estimates of (co)variance components for direct and maternal additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 22 publications
8
27
0
Order By: Relevance
“…Unlike most other studies, where piglets born alive which die shortly after birth are classified as stillborn piglets, the current study only included piglets born dead. Birth weight becomes a major factor for survival in early lactation (Mesa et al, 2006). Our result was in agreement with Leenhouwers et al (2001), who found independence between farrowing survival and birth weight in a study where farrowing was carefully supervised.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike most other studies, where piglets born alive which die shortly after birth are classified as stillborn piglets, the current study only included piglets born dead. Birth weight becomes a major factor for survival in early lactation (Mesa et al, 2006). Our result was in agreement with Leenhouwers et al (2001), who found independence between farrowing survival and birth weight in a study where farrowing was carefully supervised.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in the successful divergent selection experiment for BW in rabbits by Bolet et al (2007), a favourable correlated response for litter size at weaning and for survival from birth to weaning was also observed, but differences between lines in litter size at birth were inappreciable. Other authors have also reported higher mortality on heterogenous litters than on homogenous ones in rabbits (Poigner et al 2000) and in pigs (Mesa et al 2006). Argente et al (2012) found that environmental variance of litter size appeared to be negatively correlated with litter size after three generations of divergent selection in rabbits, showing that the relationship between homogeneity and litter size must to be studied in each case.…”
Section: Discussionmentioning
confidence: 87%
“…Anyway, nature is probably much more complex than the pure additive model fitted to analyse the variability, and it seems that this particular model somehow fails in this type of trait. In fact, when thinking of the possible causes of the efficacy of the selection process, multiple causes are at play such as those related to the morphology of the uterus (Bolet et al 2007), litter size , survivability (Mesa et al 2006) and many more other causes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with literature estimates is difficult because of the different structures of data sets and different models. In many studies, mortality traits were modeled with linear models (van Arendonk et al, 1996;Knol et al, 2002;Mesa et al, 2006), which ignore the categorical nature of those traits. Also, animals in this study were crossbreds, and some traits in crossbred populations have lower heritabilities than in purebred populations (Lutaaya et al, 2001).…”
Section: Resultsmentioning
confidence: 99%